Using Online Media for Extensive Listening Practices: Students’ Self-Reflections from the Extensive Listening Logbook - Siti Rahimah Yusra; Rizaldy Hanifa (Fakultas Bahasa dan Seni UNP, 2023)
Despite the fact that technology and online media’s great contributions on extensive listening practices, students who are unaccustomed to such activities would find the practice challenging. The current study investigated 20 first-semester university students undertaking extensive listening practices which were recorded into logbooks. The researchers aimed to map out students’ reflections on challenges and satisfaction towards the media and listening practices under a descriptive qualitative research, utilizing document analysis. Results of data analysis shows that the freedom of choice given to students while undertaking extensive listening activities through online media brought positive responses on the overall students’ satisfaction on the listening practice. Nevertheless, the unsorted levels of difficulty, unfamiliar words, foreign accents, and speed of speech from the media became the barriers mostly encountered in understanding the language contents. Furthermore, unsatisfactory listening experiences were also reported by a few students. Thus, it is advisable that teachers who implement extensive listening practices to offer help for learners to be more aware of their current and future potential to make sure learning more efficiently. It is highly expected that through frequent interactions with the listening inputs from various sources, students would enhance their metacognitive strategies to have better control of their learning.